Signs of Secular Trends in Cephalometric Characteristics of Tengger and Java People - Rio Sofwanhadi; Kunio Abe (Faculty of Dentistry, Universitas Indonesia, 2015)
A cephalometric survey on the people of the areas Tengger, rural Blitar (East Java), rural Kudus (Central Java) and Cililin (West Java) people was conducted in 1980. One of the conclusions of the survey was that the four groups of these populations in Java were homogenous in all their cranial cephalometric parameters except both genders of Tengger people had significantly with the other groups in their head length parameter and head indices. Both genders of Tengger people had significantly longer head parameter and head indices than the other groups. A similar cephalometric survey, with the same methodology, to the same area but the sample was taken out of different generation population, was again conducted on Tengger people and rural Blitar people in 2000, with the idea to check the presence of early signs of secular trend in cephalometric measurements. Computation of data was done resulting in arithmetic means and standard deviation values. Statistical analysis was conducted to compare the means of parameters of the two surveys, using 't'test, resulting in significant differences (positive trend) in head breadth, bigonial breadth of all population groups, while negative trend was seen in bizygomatic breadth of all population groups. Negative trends were als seen in facial soft tissue parameters of Blitar people, while positive trend was seen in male Tengger facial soft tissue parameters.